Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Square Terhadap Pemahaman Konsep Matematika Peserta Didik Kelas VIII SMP Negeri 2 Kamang Magek - REZI RAHMI FITRI (Jurnal Edukasi dan Penelitian Matematika, 2020)
Understanding mathematical concepts is a basic ability should be achieve by students, In fact understanding mathematical concepts in grade VIII students of SMPN 2 Kamang Magek  still relatively low and students do not play an active role in learning. The solution to this problems applied cooperative learning model Think Pair Square (TPSq) type. The purpose of this research to describe the difference understanding mathematical concepts of students in class VIII of SMPN 2 Kamang Magek who learn with cooperative learning model TPSq type and those who learn using conventional learning. This research are both descriptive research and  quasi-experiment research with static group design. Based on data analysis, P-value = 0.039 obtained that  is rejected, meaning that the understanding  mathematical concepts students who learn with cooperative learning model TPSq type is better than those who learn with conventional learning. Keywords –  conventional learning, cooperative learning model TPSq type, Understanding mathematical concepts.